Epidemiology of candidemia in lung transplant recipients and risk factors for candidemia in the early posttransplant period in the absence of universal antifungal prophylaxis. Issue 2 (28th February 2022) - Marinelli, Tina; Pennington, Kelly M.; Hamandi, Bassem; Donahoe, Laura; Rotstein, Coleman; Martinu, Tereza; Husain, Shahid
Abstract: Background: Lung transplant recipients are at increased risk of candidemia, especially in the early posttransplant period. However, the specific predisposing factors have not been established. The natural history of candidemia after lung transplantation, in the absence of universal antifungal prophylaxis, is not known. Methods: We retrospectively examined the epidemiology of candidemia at any time posttransplant in patients who underwent lung transplantation at our center between 2016 and 2019. We undertook a case‐control study and used logistic regression to evaluate the risk factors for candidemia during the first 30 days posttransplantation. Results: During the study period 712 lung transplants were performed on 705 patients. Twenty‐five lung transplant recipients (LTRs) (3.5%) experienced 31 episodes of candidemia. The median time to candidemia was 19.5 days (IQR 10.5–70.5), with 61.2% ( n = 19) episodes of candidemia occurring within the first 30 days posttransplantation. Pretransplant hospitalization, posttransplant ECMO, and posttransplant renal replacement therapy were associated with an increased risk of candidemia in the first 30 days posttransplant. Of those with candidemia in the first 30 days, 31.2% died within 30 days of the index positive blood culture. Candidemia was associated with decreased survival within 30 days posttransplant. Conclusion: This study highlights the greatest risk period of lung transplant recipients for development of candidemia and identifies several factors associated with increased risk of candidemia. These findings will help guide future studies on antifungal prophylaxis.